Magnetostratigraphy and geochronology of northwest Iceland (Dataset) ... - McDougall, Ian; Kristjansson, Leo; Saemundsson, Kristjan (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Magnetostratigraphy and geochronology of northwest Iceland ...